(3HTGQI GdeDefjf aj GdCNdGbs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg QSGdI dWjaI ai , HjGf eG hQO ef GdJhGH Ydi YHGOI Gdedc GdhgGH hSejJgG HTGQI GdeDefjf HGdahR hGdfLGI hGdaVd GdeHjf s
(3BNQgG (B:s
(3hCf jjSQ dfG CehQfG eY GdQGMI dbdhHfG hCHOGffG hCf jLYd BNQ cdGefG ef GdOfjG bhd dG Edg EdG Gddg eMeO QShd Gddg hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ HCHhGH GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdJUha hGdBOGH GdTQYjIs